2018
DOI: 10.1155/2018/3898479
|View full text |Cite
|
Sign up to set email alerts
|

Carbon-Based Materials for Thermoelectrics

Abstract: This article reviews the recent progress towards achieving carbon-based thermoelectric materials. A wide range of experimental and computational studies on carbon allotropes and composites is covered in this review paper. Specifically, we discuss the strategies for engineering graphene, graphene nanoribbon, graphene nanomesh, graphene nanowiggle, carbon nanotube (CNT), fullerene, graphyne, and carbon quantum dot for better thermoelectric performance. Moreover, we discuss the most recent advances in CNT/graphen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 236 publications
(309 reference statements)
0
28
0
Order By: Relevance
“…It has been observed that vaCNTs are perfect for that type of application, because they provide maximum heat conductivity, and thanks to the possibility to develop them, for example, on a Si surface, the result is a forest with a relatively significant packing density, thus providing better heat transmission capacity. Additionally, they are characterized by good chemical stability and low coefficient of thermal expansion [85]. Another important thing is that their transverse elastic modulus is low.…”
Section: Practical Use Of Cnts In Thermal Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been observed that vaCNTs are perfect for that type of application, because they provide maximum heat conductivity, and thanks to the possibility to develop them, for example, on a Si surface, the result is a forest with a relatively significant packing density, thus providing better heat transmission capacity. Additionally, they are characterized by good chemical stability and low coefficient of thermal expansion [85]. Another important thing is that their transverse elastic modulus is low.…”
Section: Practical Use Of Cnts In Thermal Devicesmentioning
confidence: 99%
“…The published studies on the application of nanotubes as thermoelectric devices were mainly associated with the possibility to improve the capacity of that type of systems through modification of nanotubes, e.g., through doping with imidazoles [94], diazonium salts [95], sodium-or potassium-crown ether complex [96,97], benzyl viologen or triethyloxonium hexachloroantimonate [93,96,98], encapsulated Co molecules [99] or C60 [95] into CNTs, and others. More information on thermoelectric materials based on CNTs and various modifications can be found in the review articles by Blackburn et al [4], Chakraborty et al [100], Yang et al [1], Yamamoto and Fukuyama [101].…”
Section: Practical Use Of Cnts In Thermal Devicesmentioning
confidence: 99%
“…In Equation (2), n is the number of moles of transferred electrons, f is the Faraday constant, and ∆G is the maximum thermodynamic work that can be obtained from the partition functions of the system using quantum computational calculations [30][31][32][33][34][35].…”
Section: Of 11mentioning
confidence: 99%
“…The dominant reinforcing fibres used in automotive, aerospace, and marine applications are carbon, glass, and kevlar [ 3 ]. In this framework, carbon-based (nano)materials have been widely applied in the fields of environmental science [ 4 , 5 , 6 ], food industry [ 7 ], new transportation solutions [ 8 ], medicine [ 9 ] and health applications [ 10 , 11 ], energy [ 12 , 13 ], construction [ 14 ], electronics, sports, and so on. In addition, they have gained considerable ground in high-performance applications, such as the aerospace [ 8 , 15 ], marine [ 16 ], military [ 17 ], and automobile industries [ 18 ].…”
Section: Introductionmentioning
confidence: 99%